Are Current UK Coastal Defences Good Enough for Tomorrow? An Assessment of Vulnerability to Coastal Erosion. Issue 2 (14th March 2022) - Kantamaneni, Komali; Rice, Louis; Du, Xiaoping; Allali, Belqais; Yenneti, Komali
Abstract: Coastal vulnerability and its physical, economic and social consequences at national and international scales is of high scientific, political and policy interest. Anthropogenic climate change and coastal erosion threaten the very fabric of a society. Indications, that coastal hazards are impacting diverse coastal areas severely across the world, and it is no longer a vague future threat that can't be ignored. Rising eustatic sea levels synthesized by the growing frequency and scale of coastal hazards like storm surges, coastal erosion and coastal landslides threaten low-lying and unprotected coastal areas in the United Kingdom even if they have coastal defenses. However, there is still significant uncertainty about the degree of vulnerability along different coastal stretches, particularly in England. To fill this uncertainty, the current study estimated the coastal vulnerability of the coastal erosion hotspot Camber, England, by establishing a coastal vulnerability index. This index was developed by compounding various existing parameters and termed as Erosion Coastal Vulnerability Index (ECVI). Results illustrate that 67% of coastal area fall between high and very high vulnerability categories, and current coastal defenses are not strong enough to tackle the severe coastal erosion in Camber. Within the evaluation, thematic maps were generated to enable the intensity of the vulnerability for different coastal stretches to be identified. The evaluated vulnerable hotspot should be treated urgently by regional and national policy organizations to ameliorate the impacts of coastal erosion and other associated risks. Without action, the hotspot is likely to encounter unprecedented new vulnerabilities, disasters and humanitarian catastrophes. The current study results allow for a local, regional and national comparison that may help to evaluate changes in coastal erosion vulnerability.